2016
DOI: 10.2196/mental.5324
|View full text |Cite
|
Sign up to set email alerts
|

The Preference for Internet-Based Psychological Interventions by Individuals Without Past or Current Use of Mental Health Treatment Delivered Online: A Survey Study With Mixed-Methods Analysis

Abstract: BackgroundThe use of the Internet has the potential to increase access to evidence-based mental health services for a far-reaching population at a low cost. However, low take-up rates in routine care indicate that barriers for implementing Internet-based interventions have not yet been fully identified.ObjectiveThe aim of this study was to evaluate the preference for Internet-based psychological interventions as compared to treatment delivered face to face among individuals without past or current use of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
100
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 32 publications
18
100
1
Order By: Relevance
“…This is supported by previous German surveys reporting even lower rates of e-awareness (14.0-27.3%; [42,52,64,74]). Experience with seeking psychological help formats was also a determinant of preferences, which is consistent with other studies [29,31]. Results also suggest that attachment avoidance was associated with a higher preference for guided and unguided self-help via internet interventions, and very low preference for VCP.…”
Section: Preference For Specific Delivery Formatssupporting
confidence: 89%
See 3 more Smart Citations
“…This is supported by previous German surveys reporting even lower rates of e-awareness (14.0-27.3%; [42,52,64,74]). Experience with seeking psychological help formats was also a determinant of preferences, which is consistent with other studies [29,31]. Results also suggest that attachment avoidance was associated with a higher preference for guided and unguided self-help via internet interventions, and very low preference for VCP.…”
Section: Preference For Specific Delivery Formatssupporting
confidence: 89%
“…Some recent studies identified a preference for traditional (face-to-face) over internet-based treatment (e.g. [28,29,31,[44][45][46][47]) and for therapist-guided over unguided eMHS (e.g. [28,29,33]).…”
Section: E-preferencementioning
confidence: 99%
See 2 more Smart Citations
“…Other populations have reported a preference for internet-based mental health support interventions, citing that these are better able to assure anonymity, easier and more flexible to access, and less embarrassing and shameful to use (Wallin, Mattsson et al 2016). Additionally, these populations also report that they feel more able to express feelings, self-disclose and be honest within an online intervention.…”
Section: Introductionmentioning
confidence: 99%